Effect of pour-on alphacypermethrin on feed intake, body condition score, milk yield, pregnancy rates, and calving-to-conception interval in buffaloes,. Issue 4 (1st April 2015) - Bifulco, G.; Veneziano, V.; Cimmino, R.; Esposito, L.; Auletta, L.; Varricchio, E.; Balestrieri, A.; Claps, S.; Campanile, G.; Neglia, G.
Abstract: The aims of this study were to assess the efficacy of alphacypermethrin (ACYP) on pediculosis due to Haematopinus tuberculatus and to evaluate the influence of the treatment on productive and reproductive performance in buffaloes ( Bubalus bubalis ) reared in an intensive system. The trial was performed on 56 pluriparous buffaloes at 86.8 ± 8.1 d in milk. The animals underwent individual louse count and were divided into 2 homogenous groups according to louse count, age, number of lactations, days in milk, live BW, BCS, pregnancy status, and milk yield. Group A ( n = 28) was treated by a pour-on formulation of ACYP, and Group S ( n = 28) was treated by pour-on saline solution. Individual louse counts were performed weekly on 10 buffaloes in each group. Feed intake was recorded daily and the total mixed ration, individual ingredients, and orts were analyzed to calculate DM ingestion. Individual milk yield was recorded daily and milk samples were analyzed at the beginning of the trial, after 4 wk, and at the end of the trial to assess milk composition. Individual BCS was also evaluated simultaneously. Finally, the animals underwent synchronization of ovulation starting 4 wk after treatment and the pregnancy rate and the calving–conception interval were evaluated. Data were analyzed by the Mann–Whitney test and ANOVA for repeated measures. The infestation was constant in Group S, whereas no lice were present in Group A throughout the study. Daily DMI was similar in the 2 groups (16.7 ± 0.4 vs. 16.3 ± 0.3 kg/d in Group A vs. Group S, respectively), although buffaloes in Group A showed higher ( P < 0.05) BCS score at the end of the trial (7.39 ± 0.1 vs. 7.14 ± 0.1 in Group A vs. Group S, respectively). The average milk yield/buffalo was higher ( P < 0.05) in Group A compared to Group S (10.58 ± 0.1 vs. 10.39 ± 0.1 kg in Group A vs. Group S, respectively) and this was mainly due to the higher milk production recorded in buffaloes at less than 75 d in milk (11.81 ± 0.1 vs. 11.45 ± 0.1 kg in Group A vs. Group S, respectively). Despite of a similar fertility rate (90.5 vs. 80.9% in Group A vs. Group S, respectively), a lower ( P < 0.05) calving–conception interval was recorded in Group A compared to Group S (118 ± 16 vs. 177 ± 16 d in Group A vs. Group S, respectively). In addition to the pour-on treatment against pediculosis, productive and reproductive performance were also improved. This represents a significant improvement in dairy buffalo herd management.